Study protocol: young carers and young adult carers in Switzerland - Agnes Leu; Corinna Jung; Marianne Frech; Joe Sempik; Urs Moser; Martin Verner; Saul Becker (BMC, 2018)
Abstract Background In Switzerland, the issue of young carers and young adult carers - young people under the age of 18 and 24 respectively, who take on significant or substantial caring tasks and levels of responsibility that would usually be associated with an adult - has not been researched before. The number of these younger carers is unknown, as is the extent and kind of their caring activities and the outcomes for their health, well-being, psycho-social development, education, transitions to adulthood, future employability and economic participation. Methods The project is comprised of three stages:1.A national Swiss-wide online survey to examine awareness of the issue of younger carers amongst professional populations in the education, health and social services sectors;2.An online survey of 4800 Swiss pupils in schools using standardised instruments to identify the proportion and characteristics of pupils who are carers; and3.Semi-structured interviews with 20 families comprising family members with care needs and younger carers, to consolidate and validate the other stages of the study; and to hear directly from care-dependent family members and younger carers about their experiences of the issues identified in the surveys and in previous published research. Discussion The needs of younger carers and their ill and disabled family members in Switzerland have not been systematically investigated. This will be the first study in the country to investigate these issues and to develop evidence-based recommendations for policy and practice, drawing also on international research. The present study therefore fills an important national and international research gap. It will collect important data on the awareness, extent, kind and impact of caring amongst children and young people in Switzerland, and cross-link these findings with robust evidence from other countries. The study will reveal (a) the extent of awareness of the issue of young carers amongst medical, social, health, educational, and other groups in Switzerland; (b) the proportion and number of young carers amongst a normative child population, and what these young carers 'do' in terms of their caring roles; and (c) direct accounts by families of their care-giving and receiving experiences.